Long Non-coding RNA 332443 Inhibits Preadipocyte Differentiation by Targeting Runx1 and p38-MAPK and ERK1/2-MAPK Signaling Pathways - Xiao, Fen; Tang, Chen-Yi; Tang, Hao-Neng; Wu, Hui-Xuan; Hu, Nan; Li, Long; Zhou, Hou-De (Frontiers in Cell and Developmental Biology, 2021)
Long noncoding RNAs (lncRNAs) have emerged as integral regulators of pathophysiological process, but their specific roles and mechanisms in adipose tissue development remain largely unknown. Here, through microarray analysis, co-expression, and tissue specific analysis of adipocyte tissues after fasting for 72 hours, we found that Lnc-FR332443 expression was dramatically decreased, as well as the expression of Runx1. The UCSC database and Ensembl database showed that Lnc-FR332443 is the antisense lncRNA of Runx1. Lnc-FR332443 and Runx1 are highly enriched in adipose tissue and downregulated during adipogenic differentiation. Adipose tissue-specific knockdown of Lnc-FR332443 increased fat mass in vivo, and specific knockdown of Lnc-FR332433 in 3T3-L1 preadipocytes promoted adipogenic differentiation. In this process, Runx1 expression was decreased when Lnc-FR332443 was downregulated in adipocytes or 3T3-L1 preadipocytes or increased after Lnc-FR332443 was upregulated in 3T3-L1 preadipocytes. However, after Runx1 was overexpressed in adipocytes, the expression levels of the adipocyte cell marker genes PPARγ, C/EBPα and FABP4 were obviously decreased, while Lnc-FR332443 expression was not significantly changed. Mechanistically, Lnc-FR332443 positively regulates Runx1 expression in mouse adipocytes and suppresses adipocyte differentiation by attenuating the phosphorylation of MAPK-p38 and MAPK-p-ERK1/2 expression. Our results indicated that Lnc-FR332433 inhibits adipogenesis and might be a drug target for the prevention and treatment of obesity.